Protest and the urban guerrilla - Clutterbuck, Richard L. (London, Cassell, 1973)
An examination of the whole spectrum of protest and violence in the Western countries.
Britain : a non-violent society: Protest, violence and change. The story of protest in England. Protest and the police. Riot control -- Northern Ireland : a violent contrast: A new revolutionary challenge. Civil rights and violence. From communal riots to urban guerrilla warfare. Internament and interrogation. A peak of terror. Bloody Sunday. Direct rule -- The spread of dissent and violence: Revolution : international or internal. The professionals. The Marxist dissenters. The Alternative Society and the pressure groups. Revolutionary students and revolutionary dons. Intellectuals and the shop floor. Urban guerrillas across the world -- The future: The pattern of revolutioon and backlash. Prospect for Britain.
Includes bibliographical references and index.
Keywords: Political violence -- Great Britain; terrorism; Political violence; Great Britain; Northern Ireland; Political violence; Political violence -- Great Britain; Political violence -- Northern Ireland